Pengaruh Diabetes Self Management Education (DSME) Terhadap Peningkatan Pengetahuan pada Penderita Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Pariaman Kota Pariaman Tahun 2022 - Marni, Linda; Armaita, Armaita; Yoselina, Prima; Anggita, Kheniva Diah (Jurnal Kesehatan Komunitas, 2025)
Diabetes mellitus (DM) is now growing into a global health problem. The International Diabetes Federation (IDF) shows that the prevalence of DM in the world is estimated to increase from 536,6 million cases (10,5%) in 2021 to 783,2 million (12,2%) in 2045. The number of DM cases in Pariaman City in 2021 was 978, with the highest number at the Pariaman Health Center (201 cases). Of the 22 villages in the Pariaman Health Center work area, the highest number of DM cases was obtained in Kampung Baru village (36 cases). The purpose of this study is to determine the effect of diabetes self-management education (DSME) on increasing the knowledge of people with type 2 diabetes mellitus in the work area of the Pariaman Health Center, Pariaman City, in 2022. This study is a quasi-experimental research with a one-group pretest and posttest design. The sampling technique was a total sampling of 36 respondents. The research was conducted in Kampung Baru village, the working area of the Pariaman Health Center, from June 27 to August 6, 2022. Data collection tools are carried out using questionnaires and computerized data processing. The results of the study showed that there was an increase in respondents' knowledge after being given the DSME intervention, from 61.1% to 86.1%. In addition, it was also found that there was an effect of DSME intervention on increasing knowledge in patients with type 2 diabetes mellitus in the Pariaman City Health Center Working Area in 2022 (p-value = 0.000 < 0.05). It is hoped that people with diabetes mellitus will know how to manage their diabetes mellitus care so that their sugar levels can return to normal and stable.